The role of formative objective structured clinical examinations on students’ performance in clinical years - Riaz, Misbah; Hussain, Fazal; Khan, Mah Muneer (International Journal of Research in Medical Sciences, 2021)
Background: Objective structured clinical examinations are the gold standard of modern medical assessment for students. The aim of our study was to determine the effect of formative OSCEs on students’ performance in summative OSCEs in final year medical exams. Methods: This observational study was conducted at surgical B Unit, MTI, Khyber teaching hospital, Peshawar from January to December 2019. A total of 297 consecutive students of final year MBBS, studying in Khyber medical college were included in the study. Students who had repeated the year were excluded. Examination scores of formative OSCEs taken in the ward and the subsequent summative OSCEs taken in the subject of surgery were analyzed to determine the effect on summative OSCE performance. Data was analyzed using SPSS 23. Chi square test was used and p>0.05 was taken as statistically significant. Results: Out of 297 students, 188 (63.3%) were males and 109 (36.7%) were females. Of these, 243 (81.8%) students appeared in the formative OSCEs whereas 54 (18.2%) students did not appear in the formative OSCEs. The result of the subsequent summative OSCEs showed that those students who appeared in formative OSCEs showed a better performance in summative OSCEs (p<0.001) with majority of students (53.5%) having scores above 80%. Conclusions: Formative OSCEs enhance students’ performance in summative OSCEs. Repetitive formative OSCE sessions along with regular feedback should be incorporated in the medical curriculum for better performance of medical students in their final year undergraduate exams.